Physicochemical, textural, rheological and microstructural properties of protein isolate gels produced from European eel (Anguilla anguilla) by heat-induced gelation process - Taktak, Warfak; Nasri, Rim; Hamdi, Marwa; Gómez-Mascaraque, Laura G.; López-Rubio, Amparo; Li, Suming; Nasri, Moncef; Karra-Chaâbouni, Maha (Food Hydrocolloids, 2018)
This study investigates the preparation and characterization of a protein isolate extracted from European eel (Anguilla anguilla) and its ability to generate protein gel. European eel protein isolate (EPI) was extracted from European eel muscle by a pH-shifting process. European eel protein isolate gels (EPIGs) were prepared by heat treatment of EPI with varying gelling parameters. The influences of pH value (2.0 and 10.0), EPI concentration (7 and 10%) and ionic strength on biochemical, textural, rheological and microstructural properties of EPIGs were studied. Textural and physicochemical analysis demonstrated a different gel forming mechanism for acidic and alkaline-treated gels. Results showed that whiteness of EPIGs increased with decreasing of EPI concentration and pH values. Moreover, EPIGs prepared under alkaline conditions were characterized by higher water holding capacity and total pigment content. In addition, the acid EPIGs exhibited poorer gelling ability compared to alkali EPIGs. Thus, a more compacted gel-protein arrangement was formed under alkaline condition. Furthermore, addition of salt slightly improved the elasticity of EPIGs at 2% wt. concentration. FT-IR analysis of EPIGs revealed more irregular secondary structure and higher hydration level in the acid EPIGs compared to alkaline EPIGs. Thus, this study shows the potential of protein isolate gels from A. anguilla as food texture enhancers. This study was funded by the Ministry of Higher Education and Scientific Research, Tunisia. Authors would also like to thank the Central Support Service for Experimental Research (SCSIE) of the University of Valencia for the electronic microscopy service. Peer reviewed